INFORMASI INDUSTRI KECIL DAN MENENGAH (IKM) DI KABUPATEN PIDIE BERBASIS SISTEM INFORMASI GEOGRAFI - Yuswardi Yuswardi; Arrayyani Arrayyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Existence small industry in the district of Pidie there are many people who build small businesses at home in this case already many people do not use the existence of business one there must be an information system for the community location of small businesses and intermediate(IKM).Currently Quantum GIS technology can be built web-based Quantum GIS is a form of website that describes about the geographical information of anarea, The existence of intermediatehas become an income for the community layer of small entrepreneurs with the creation of jobs such as household industries, then by itself has reduced society from unemployment. District batee, Mutiara, and Pidie in pidie district. So in this study designed application Quantum GIS on small businesses and intermediate in the district of Pidie using quantum GIS, create a digital map of thelocation of small businesses and intermediate in the district of Pidie and display information through a digital map of the location of the place of existence small businesses and intermediatein the district of Pidie facilitate the community or customers in heading to the location With this system can manage the data on the location map of the existence of small businesses and intermediate in utilizing quantum gis facilities as a map of the location of IKM map,klibeut, batee and application design results are only implemented a quantum.Keywords : Geografis Information System (GIS), IKM, Quantum GIS.